What Is the Economic Benefit of a Citrus Health Management Area (CHMA)? A Case Study - Ariel Singerman; Brandon Page (EDIS)
A Citrus Health Management Area (CHMA) is a group of growers who work cooperatively to coordinate insecticide application timing and mode of action in order control the insect vector of citrus greening disease. CHMAs help prevent insect vectors from moving between groves and reduce the likelihood that insects will develop pesticide resistance. This 3-page fact sheet analyzes the case-study data on yields of Valencia oranges from blocks located in two different categories of CHMAs to find the impact of citrus greening disease on citrus yields and provide evidence on the effectiveness of best class CHMAs as a way to deal with the disease. The analysis provides evidence that CHMAs can enhance an individual grower’s profitability at a time when margins are becoming increasingly narrow. Written by Ariel Singerman and Brandon Page, and published by the Food and Resource Economics Department, February 2016.